Optical recording of neuronal activity with a genetically-encoded calcium indicator in anesthetized and freely moving mice - Lütcke, Henry; Murayama, Masanori; Hahn, Thomas; Margolis, David J.; Astori, Simone; Meyer, Stephan; Göbel, Werner; Yang, Ying; Tang, Wannan; Kügler, Sebastian; Sprengel, Rolf; Nagai, Takeharu; et al. (Frontiers in Neural Circuits, 2010)
Fluorescent calcium (Ca2+) indicator proteins (FCIPs) are promising tools for functional imaging of cellular activity in living animals. However, they have still not reached their full potential for in vivo imaging of neuronal activity due to limitations in expression levels, dynamic range, and sensitivity for reporting action potentials. Here, we report that viral expression of the ratiometric Ca2+ sensor yellow cameleon 3.60 (YC3.60) in pyramidal neurons of mouse barrel cortex enables in vivo measurement of neuronal activity with high dynamic range and sensitivity across multiple spatial scales. By combining juxtacellular recordings and two-photon imaging in vitro and in vivo, we demonstrate that YC3.60 can resolve single action potential (AP)-evoked Ca2+ transients and reliably reports bursts of APs with negligible saturation. Spontaneous and whisker-evoked Ca2+ transients were detected in individual apical dendrites and somata as well as in local neuronal populations. Moreover, bulk measurements using wide-field imaging or fiber-optics revealed sensory-evoked YC3.60 signals in large areas of the barrel field. Fiber-optic recordings in particular enabled measurements in awake, freely moving mice and revealed complex Ca2+ dynamics, possibly reflecting different behavior-related brain states. Viral expression of YC3.60 – in combination with various optical techniques – thus opens a multitude of opportunities for functional studies of the neural basis of animal behavior, from dendrites to the levels of local and large-scale neuronal populations.